2015
DOI: 10.1007/s40617-015-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Latency-Based FA as Baseline for Subsequent Treatment Evaluation

Abstract: No research has used latency-based functional analysis (FA) outcomes as baseline data from which to evaluate the effectiveness of subsequent function-based treatments. This approach to analysis calls for the continued collection of latency-based measures for all targeted variables throughout all phases of treatment. We tracked client progress during treatment using latency-based, rate-based, and percentage-ofopportunity measures of relevant behavior and compared graphical representations of each. Visual inspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Together with those of previous research (e.g., Neidert et al, 2013;Thomason-Sassi et al, 2011), these findings suggest that latency to problem behavior is an effective measure of response strength during FAs. Furthermore, the findings of this study add to the small body of literature evaluating latency measures during treatment evaluations (e.g., Caruthers et al, 2015;Dozier et al, 2011;Roscoe et al, 2010). Finally, these findings identify some limitations of basing treatment decisions solely on latency measures and provide preliminary data to support the use of hybrid procedures when conducting treatment analyses of severe problem behavior.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Together with those of previous research (e.g., Neidert et al, 2013;Thomason-Sassi et al, 2011), these findings suggest that latency to problem behavior is an effective measure of response strength during FAs. Furthermore, the findings of this study add to the small body of literature evaluating latency measures during treatment evaluations (e.g., Caruthers et al, 2015;Dozier et al, 2011;Roscoe et al, 2010). Finally, these findings identify some limitations of basing treatment decisions solely on latency measures and provide preliminary data to support the use of hybrid procedures when conducting treatment analyses of severe problem behavior.…”
Section: Discussionmentioning
confidence: 62%
“…These termination criteria allow experimenters to evoke and reinforce the targeted problem behavior while minimizing the overall number of occurrences. Latency-based FAs have been used to identify maintaining variables for a variety of problem behaviors including self-injury (Thomason-Sassi et al, 2011), aggression (Caruthers, Lambert, Chazin, Harbin, & Houchins-Juarez, 2015;Roscoe, Kindle, & Pence, 2010), elopement (Neidert, Iwata, Dempsey, & Thomasson-Sassi, 2013), and foot-shoe fetish (Dozier, Iwata, & Worsdell, 2011).…”
Section: Recent Research Has Demonstrated the Utility Of Latency Measmentioning
confidence: 99%
“…Currently, data exist highlighting the positive effect of interventions informed by the results of latency‐based FAs (e.g., Caruthers et al, ; Davis et al, ; Lambert, Finley, & Caruthers, ). However, consecutive case series evaluations have not yet been conducted across individuals, populations, and behaviors (cf.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative approach within trial‐based FA includes measuring latency to problem behavior as the primary dependent variable and extending the observation period to 5 or 10 min. Data obtained through latency‐based FAs have served as both an indication of behavior function (Thomason‐Sassi et al, ) and a measure of baseline performance for evaluating function‐based interventions (Caruthers, Lambert, Chazin, Harbin, & Houchins‐Juárez, ). Nevertheless, little research has demonstrated practical applications of latency‐based FAs in applied settings.…”
mentioning
confidence: 99%
“…Recently, latency to challenging behavior has been used as a measure in functional analyses for individuals with intellectual and developmental disabilities; this is referred to as latency‐based functional analysis (LFA; Call, Pabico, & Lomas, ; Caruthers, Lambert, Chazin, Harbin, & Houchins‐Juarez, ; Thomason‐Sassi, Iwata, Neidert, & Roscoe, ). In LFA, sessions follow the same procedures as standard functional analyses (SFAs), but sessions are terminated when the target behavior occurs and the programmed consequence is delivered.…”
Section: Introductionmentioning
confidence: 99%